THE COURSE OF NORMAL PHYSIOLOGY USING THE PRINCIPLE OF THE THEORY OF FUNCTIONAL SYSTEMS - V. V. Andrianov; N. A. Vasilyuk; K. V. Sudakov (Сеченовский вестник)
During learning, parallel with physiology of separate organs, the students get to know self-regulating functional systems, which determine homeostasis, behavioral and psychical activity. Theory of functional systems orientates the students understanding of mechanisms of steadiness of different physiology indices during different influences on organism. We consider that the theory of functional systems is a theoretical base of care of public health and has, to our mind, as the same significance as clinical training of the students.